The role of exosomes in the mechanisms of inflammation development in patients with cardiovascular pathology and the contribution to therapeutic potential of stem cells - P. F. Muzychenko; Zh. M. Minchenko; T. I. Havrylenko; V. A. Cherniak; S. V. Demidov; N. O. Ryzhkova; O. A. Pidhaina (Zaporožskij Medicinskij Žurnal)
The aim – based on the analysis of the scientific literature focused on understanding the role of exosomes in the mechanisms of inflammation development and application of stem cells for cellular therapy in different pathological conditions, to identify and substantiate the prospects of using the exosomes as prognostic markers of a disease progression and application of their therapeutic potential in cardiovascular pathology.